Nutritional and Physiological Responses of Sudan Desert Sheep and Nubian Goats to Water Restriction (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to compare the nutrient utilization,concentration of some rumen metabolites, blood urea nitrogen and somephysiological responses to water restriction in Sudan desert sheep andNubian goats. Three yearling uncastrated intact males from each species,averaging 18.37 kg (for sheep) and 13.21 kg (for goats), were randomlyallotted to four treatments in a completely randomized block design witha 2 x 2 factorial arrangement of treatments to determine the effects ofanimal species and water restriction. Both species were offered either adlibitum feed and water or water restricted to 50% of ad libitum level withad libitum feed. Animal species resulted in a significant (P